Investments in Contemporary Russian Artwork as an Alternative Form of Investment - Alexandra Galanova; Maria Lutsenko; Jorge Zamorano (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2020)
In the last decades of the 20th century, various classes of alternative investments have become increasingly popular among investors. During this time, art as a form of alternative investment attracted attention not only from potential buyers but also from academic scholars. Unfortunately, only a few of the newly published papers contained any quantitative analysis with regard to art’s investment performance. Besides, even a smaller amount of research was devoted to the analysis of Russian art markets. Therefore, the purpose of this work is to evaluate the efficiency of investments in the artworks of contemporary Russian painters and to compare the effectiveness of these investments with the effectiveness of investments in stock, bond and real estate markets in Russia and the USA. For this research, we first conduct a hedonic regression analysis on the data available for 1950-2019 time period. After that, we build a hedonic price index for the canvases of contemporary Russian artists. According to the results, the trend of this index reiterates largely the price behavior for world contemporary art market. However, the results of this study indicate that investments in contemporary Russian art do not outperform investments in instruments of Russian and American capital and real estate markets. These results were derived by applying the CAPM model which demonstrated that Russian art as a form of alternative investment is not advisable for the purposes of diversification of investment portfolios. Based on these findings, contemporary Russian art in general can be considered an unattractive instrument for Russian and foreign investors.